The Influence of Peer Counselors on Adolescent Mental Health Using the Spiritual Emotional Freedom Technique (SEFT) Method - Ulfah, Bardiati; Aulia, Fika; Agustina, Yaolanda Rizqi; Padlillah, Rahmi; Salsabilla, Anggun; Nazwa, Alya (Yayasan Rumah Ilmu Professor, 2026)
Adolescence is a transitional phase of self-discovery and lifestyle adjustments that can cause stress. Mentally healthy adolescents are those who are able to cope with life's pressures, be productive, and contribute to their communities. According to the 2024 I-NAMHS survey, 15.5-2.45 million adolescents have mental health problems, with the highest prevalence being 14 years old (75%). Mental health problems in adolescents, such as stress and anxiety, can hinder physical activity and quality. Mental health is crucial for adolescents, with psychoeducation to build a strong mental character, one of which is through peer counselors. The Spiritual Emotional Freedom Technique (SEFT) method as an educational medium has proven to be effective in addressing adolescent mental health issues. The purpose of this study was to determine the influence of peers using the SEFT method approach on adolescent mental health. The method used was a Quasi-Experimental Design with a Pretest Posttest Control Group design. The results showed a significant influence of the SEFT method by peers on improving the emotional mental state of adolescents in the depression category with a t-test p value of 0.015, while in the anxiety and stress problem categories there was no influence of the SEFT method given by peers. The approach of those closest to them with continuous education through beneficial spiritual methods has an impact on the continuation of a generation of mentally and physically healthy adolescents.